Determination of oxidative stress levels and some antioxidant enzyme activities in prostate cancer. (3rd July 2019) - Ahmed Amar, Safa Ali; Eryilmaz, Recep; Demir, Halit; Aykan, Serdar; Demir, Canan
Abstract: In this study, the antioxidant enzyme activities such as (SOD, GSH, and CAT) and malondialdehyde (MDA) level which is the end product of lipid peroxidation, were determined from the serum samples taken from patients diagnosed with prostate cancer Van Yuzuncu Yıl University Medical Faculty of Educational Research and Training Hospital and İstanbul Bagcilar Education Research Hospital. The SOD, GSH, and CAT activity of patient groups was found significantly lower than the healthy control group in patients with prostate cancer ( p < .05). Serum MDA level is found significantly high when compared to control groups. MDA levels increased in patients that suffer prostate cancer disorder. Whereas, firstly antioxidant enzymes activity of SOD, GSH and CAT have been decreased in control groups. Thus, we concluded that the cause of development of prostate cancer may be the result of an imbalance between the antioxidants and oxidative stress. As a result, SOD, CAT, GSH, and MDA may play an important role in the etiopathogenesis of prostate cancer.